2018
DOI: 10.4049/jimmunol.1700954
|View full text |Cite
|
Sign up to set email alerts
|

mTOR- and SGK-Mediated Connexin 43 Expression Participates in Lipopolysaccharide-Stimulated Macrophage Migration through the iNOS/Src/FAK Axis

Abstract: Connexin 43 (Cx43) deficiency was found to increase mortality in a mouse model of bacterial peritonitis, and Cx43 is upregulated in macrophages by LPS treatment. In this study, we characterized a novel signaling pathway for LPS-induced Cx43 expression in RAW264.7 cells and thioglycolate-elicited peritoneal macrophages (TGEMs). LPS alone or LPS-containing conditioned medium (CM) upregulated Cx43. Overexpression or silencing of Cx43 led to the enhancement or inhibition, respectively, of CM-induced TGEM migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Immunofluorescence staining of Cx43, CD86 and iNOS was used to investigate the effect of AngII on macrophage polarization and it was discovered that Cx43 was expressed in RAW264.7 macrophages. Moreover, some of these results are consistent with the Shen et al (36) study. In addition, AngII treatment increased the expression levels of CD86, iNOS and Cx43, which indicated that Cx43 may be involved in the M1-type macrophage polarization process.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Immunofluorescence staining of Cx43, CD86 and iNOS was used to investigate the effect of AngII on macrophage polarization and it was discovered that Cx43 was expressed in RAW264.7 macrophages. Moreover, some of these results are consistent with the Shen et al (36) study. In addition, AngII treatment increased the expression levels of CD86, iNOS and Cx43, which indicated that Cx43 may be involved in the M1-type macrophage polarization process.…”
Section: Discussionsupporting
confidence: 91%
“…Cx43 deficiency has been reported to increase mortality in a mouse model of bacterial peritonitis, and Cx43 is reportedly upregulated in macrophages following LPS treatment (36). Shen et al (36) suggested that Cx43 expression in macrophages was associated with macrophage migration, an important immune process in the host defence against infection. In addition, nie et al (37) demonstrated that the expression levels of Cx43 in mouse dendritic cells were significantly increased following AngII treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of the peritoneal macrophages from mice was conducted as described in previous studies with some minor modifications (28). Briefly, 3 days after the injection of 4% thioglycolate, macrophages were flushed from peritoneal cavity with cold Dulbecco's modified Eagle's medium (DMEM) (Gibco), and cultured in complete DMEM medium (10% FBS, 1% penicillin/streptomycin).…”
Section: Isolation Of Thioglycolate-elicited Peritoneal Macrophages (mentioning
confidence: 99%
“…Lastly, it is important to note, that the investigations into Cx43 in relation to Mϕs are limited, since the homozygous Cx43 knockout is lethal in mice due to heart failure [16,23]. These circumstances have led to studies making use of different circumventions, such as heterozygous mice [24,25], Mϕ-Cx43 specific knockout mice [9,18] and fetal liver cell transplantation from homozygous Cx43 knockout mice into irradiated recipient-mice [26], as discussed below.…”
Section: Introductionmentioning
confidence: 99%